NUMERICAL MODELING OF MOMENT METHOD FOR ANTENNA SIMULATION - Hartansky, Rene; Maga, Dusan; Siroky, Peter (International Journal of Computing, 2014)
Paper includes accuracy problems of numerical computing of wire antennas characteristics, specially resistively loaded dipoles - antennas with varying inner impedance. One may find here the modification of Pocklington’s equation (numerical computation of resistive dipole) to the form, which allows us to decrease the number of dipole segmentation elements.